2021
DOI: 10.2147/cmar.s320541
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Plasma HSP90α, Serum EBV VCA IgA Antibody and Plasma EBV DNA for the Diagnosis and Prognosis Prediction of Nasopharyngeal Carcinoma

Abstract: The aim of this study was to evaluate the effectiveness of Epstein-Barr virus (EBV) VCA-IgA antibody, EBV DNA and HSP90α alone or in combinations for the diagnosis and prognostic prediction of nasopharyngeal carcinoma (NPC). Methods: A total of 113 treatment-naïve patients with NPC and 40 healthy controls were enrolled. Plasma HSP90α and serum EBV VCA IgA antibody were detected using ELISA, and plasma EBV DNA was quantified using qPCR assay. The effectiveness of plasma HSP90α level, serum EBV VCA IgA antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In a clinical study of patients with hepatocellular carcinoma, plasma HSP90a has been found to be of diagnostic value for early hepatocellular carcinoma, and the combination of AFP can improve the diagnostic efficiency (22). We can also see the diagnostic value found in other tumor studies, such as colorectal cancer (21), nasopharyngeal carcinoma (49), lung cancer (64). In this study, plasma HSP90a in the malignant tumor group was significantly higher than that in the normal group (P < 0.001).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a clinical study of patients with hepatocellular carcinoma, plasma HSP90a has been found to be of diagnostic value for early hepatocellular carcinoma, and the combination of AFP can improve the diagnostic efficiency (22). We can also see the diagnostic value found in other tumor studies, such as colorectal cancer (21), nasopharyngeal carcinoma (49), lung cancer (64). In this study, plasma HSP90a in the malignant tumor group was significantly higher than that in the normal group (P < 0.001).…”
Section: Discussionmentioning
confidence: 81%
“…In a study of the diagnostic and prognostic value of HSP90α in gastric cancer, HSP90α of plasma was not associated with survival in patients with gastric cancer ( 48 ). While HSP90α was identified as an independent prognostic factor for nasopharyngeal carcinoma by univariate and multivariate Cox proportional risk regression analysis in a clinical study ( 49 ). A retrospective study measured HSP90α levels before and after treatment in 231 patients with lung cancer and found that HSP90α levels were associated with lung cancer treatment response and patient outcomes ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these tests are not without limitations in terms of reliability [50][51][52]. The use of viral load quantification alongside serologic tests seems to enhance sensitivity and specificity [53][54][55], although not all studies support this observation [56,57].…”
Section: Discussionmentioning
confidence: 99%